TAKARAN PUPUK KALIUM TERHADAP HASIL BERBAGAI VARIETAS KEDELAI (Glycine max (L.) Merrill) - Yudi Yusdian (Paspalum: Jurnal Ilmiah Pertanian, 2015)
The objective of this research was to study the interaction effect  between the dosage Potassium fertilizer and soybean varieties on the  yield and also to get the optimum dosage Potassium fertilizer that give maximum yield of each  soybean variety.The experiment was conducted at Tanjungwangi village, Pacet subdistrict, Bandung regency, West Java province. The altitude is about 745  m above sea level. The average of rainfall was 1963,51 mm/year and the type of rainfall is C according to Schmidt and Fergusson (1951). The soil type is Inceptisol  with pH 7,2. The experiment was conducted from Oktober 2011 until January 2012. The experiment was arranged in experimental methode to split plot design with three replications. The main plot factor is a soybean varieties (V) consisted of three varieties : v1 = Kaba, v2 = Anjasmoro and v3 = Willis, while the sub plot factor is a fertilizer dosage of K2O (K) consisting of three standards : k1 = 30 kg ha-1,  k2 = 60 kg ha-1 and k3 = 90 kg ha-1. The result showed that there was interaction effect between the dosage potassium fertilizer and soybean varieties on the number of filled pod, number of seed and seed weight per plant. The optimum dosage potassium fertilizer that could give maximum yield for each varieties :  Kaba  61,80 kg ha-1 K2O, Anjasmoro 66,60 kg   ha-1 K2O and Wilis 72,60  kg ha-1 K2O.